2009
DOI: 10.1128/jb.01170-08
|View full text |Cite|
|
Sign up to set email alerts
|

Growth Deficiencies of Neisseria meningitidis pfs and luxS Mutants Are Not Due to Inactivation of Quorum Sensing

Abstract: The activated methyl cycle (AMC) is a central metabolic pathway used to generate (and recycle) several important metabolites and enable methylation. Pfs and LuxS are considered integral components of this pathway because they convert S-adenosylhomocysteine (SAH) to S-ribosylhomocysteine (SRH) and S-ribosylhomocysteine to homocysteine (HCY), respectively. The latter reaction has a second function since it also generates the precursor of the quorum-sensing molecule autoinducer 2 (AI-2). By demonstrating that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…Previous work in other species has demonstrated elevated SRH concentrations in the culture supernatant of luxS mutant strains [40]. To test this we utilized the in vitro AI-2 synthesis reaction described above with the wildtype LuxS enzyme and the cell-free supernatant as the source of substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work in other species has demonstrated elevated SRH concentrations in the culture supernatant of luxS mutant strains [40]. To test this we utilized the in vitro AI-2 synthesis reaction described above with the wildtype LuxS enzyme and the cell-free supernatant as the source of substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Guillermo et al first showed that hydroxylated pyrrolidine represents a SAH/MTA inhibitor and speculated that these compounds might be transitional analogs (76). However, inhibition of Pfs is fatal to cells because the accumulation of MTA and SAH is toxic to cells (77,78). Excess MTA levels in cells inhibit growth processes and DNA synthesis by indirectly preventing the synthesis of polyamines involved in these important processes (79,80).…”
Section: Target the Luxs/al-2 System: New Antibacterial Strategy For mentioning
confidence: 99%
“…As an important part of the S-adenosylmethionine (SAM) cycle, methylthioadenosine/S-adenosylhomocysteine nucleosidase (Pfs) function in a broad array of metabolic reactions, such as methylation reactions; the recycling pathway of adenine, sulfur, and methionine; and the synthesis of polyamine, vitamin, and the universal quorumsensing signal, autoinducer-2 (AI-2) [19,20]. It has been reported that Pfs inhibitors disrupt AI-2 production in Vibrio cholerae and Escherichia coli in a dose-dependent manner without affecting growth and biofilm formation in these organisms [21].…”
Section: Introductionmentioning
confidence: 99%